Impak perbelanjaan kerajaan dalam pendidikan ke atas struktur buruh dan gaji berdasarkan tahap kemahiran dalam pelbagai sektor ekonomi di Malaysia: Analisis penguraian input-output - Muhammad Baqir, Abdullah (2020)
In Malaysia, government expenditure in education is one of the major expenditures. Annual growth rate of government education expenditure is relatively higher than the growth rate of skilled and semi-skilled labours for the period 1985-2017. Nevertheless, the numbers of skilled and semi-skilled labours are still inadequate to meet the need of labours in economic sectors. Therefore, this research is estimating the impact of government expenditure in education not only on the quantity but also the component expenditure on the change of labour structure based on the number and labour wage according to skill in various economic sectors from 1978-2015 by using input-output decomposition model analysis. The components of expenditure comprise of expenditure on teaching staff’s wage, educational equipment and physical assets; scholarship and study loan; and other expenditures. Government expenditure on education has a more significant impact increased number and wages of skilled labour and semi-skilled labour in service and manufacturing sectors compared to the agriculture sector because productivity in these sectors needs more skilled labour to produce goods and services. The study also shows that government expenditure on education not only success increases number and salary skilled labor and semi-skilled labor, but it also reduces the use of unskilled labour in the economy. The expenditure component on teaching staff’s wages at the secondary level is the largest contribution to skilled and semi-skilled labour compared to other expenditures because this expenditure is important to ensure the quality of education through more participation of the professional teacher. Besides, the integration of economic growth gives a positive impact on government education expenditure to increase the number of skilled and semi-skilled labours. Technical change represent as technological enhancement in the production process decreases the use of total labours in other economic sectors.